Modulation of human mesenchymal stem cells towards neuronal differentiation via physical cues from scaffold design - Leong, Wen Shing. (2013)
The influential role of physical cues from microenvironment in directing stem cell differentiation has been recognition. In spite of extensive studies reported in modulation of stem cell fate via various physical cues, little has been explored in neuronal differentiation event with either single or combination of these physical cues.